2017
DOI: 10.1039/c7ob01513e
|View full text |Cite
|
Sign up to set email alerts
|

An ortho C-methylation/O-glycosylation motif on a hydroxy-coumarin scaffold, selectively installed by biocatalysis

Abstract: Various bioactive natural products, like the aminocoumarin antibiotics novobiocin and coumermycin, exhibit an aromatic C-methyl group adjacent to a glycosylated phenolic hydroxyl group. Therefore, tailoring of basic phenolic scaffolds to contain the intricate C-methyl/O-glycosyl motif is of high interest for structural and functional diversification of natural products. We demonstrate site-selective 8-C-methylation and 7-O-β-D-glucosylation of 4,5,7-trihydroxy-3-phenyl-coumarin (1) by S-adenosyl-L-methionine d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…12 Nidetzky synthesized a new sugar-containing coumarin catalyzed by O-glycosyltransferase. 13 Some other enzymes such as BLAP (alkaline protease from Bacillus licheniformis) have also been used to synthesize coumarin. 14 The reactions catalyzed by enzymes are relatively mild; however, they always require a longer reaction time (24 h or more) to achieve the desired yields, and the enzymes needed for the reaction are difficult to obtain.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…12 Nidetzky synthesized a new sugar-containing coumarin catalyzed by O-glycosyltransferase. 13 Some other enzymes such as BLAP (alkaline protease from Bacillus licheniformis) have also been used to synthesize coumarin. 14 The reactions catalyzed by enzymes are relatively mild; however, they always require a longer reaction time (24 h or more) to achieve the desired yields, and the enzymes needed for the reaction are difficult to obtain.…”
mentioning
confidence: 99%
“…D-Glucose (4a) contains multiple hydroxyl groups, including 6-OH, 1-OH and secondary OHs. The acylation position of Dglucose was veried by 13 C NMR according to the general strategy described by Yoshimoto et al 19 The 13 C NMR data are shown in Table 3. The chemical signals for C-6a and C-6b of product 5a shied downeld from 61.20 to 65.22 ppm and those for C-5a and C-5b shied upeld from 71.80 to 69.20 ppm and from 76.70 to 73.49 ppm, respectively, while that for other C species did not change signicantly.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[27,28] Am ore step-and atom-efficient strategy is to couple cofactor formation with C-alkyl transfer. [15,27,29,35,36] Although in-depth knowledge of the substrate promiscuity of C-MTases has been garnered from structural and mutagenesis studies, [17,19,20,37] little is known about how the structural features of the SAM cofactor itself influences the yield and scope of C-alkylation. [34] ClDAi sashelf-stable,a tom-economical adenosine source for such aprocess catalyzed by SalL compared to ATP, which is asubstrate for SAM production by methionine adenosyltransferase (MAT).…”
mentioning
confidence: 99%
“…[34] ClDAi sashelf-stable,a tom-economical adenosine source for such aprocess catalyzed by SalL compared to ATP, which is asubstrate for SAM production by methionine adenosyltransferase (MAT). [15,27,29,35,36] Although in-depth knowledge of the substrate promiscuity of C-MTases has been garnered from structural and mutagenesis studies, [17,19,20,37] little is known about how the structural features of the SAM cofactor itself influences the yield and scope of C-alkylation. [14,30] Herein, we showcase am ethod to address these limitations by strategic modifications to SAM and S-adenosyl ethionine (SAE, Figure 1c).…”
mentioning
confidence: 99%